(Keynote) Electromagnetic Field Stimulated MOFs. (8th September 2020) - Knebel, Alexander; Chen, Donghui; Hosseinimonjezi, Bahram; Santos, Jaciara C. C.; Redel, Engelbert; Caro, Jürgen; Volkmer, Dirk; Wöll, Christof
Abstract : Metal-Organic Frameworks, consisting of inorganic nodes and organic linker molecules, are (mainly) porous materials with record holding inner surface areas, tailor-made properties, and adjustable pore windows. External stimuli on MOFs can be applied and achieve control over crystallization, gas transport properties, pore windows, and many other effects: breathing, dipolar moment, etc., which is extremely interesting for membrane science.The keynote will present an overview on novel types of applied physics to membrane separations to enhance green production and carbon capture: we can use novel MOF materials as porous liquids or MOF thin films and influence their properties with external stimuli, such as electromagnetic fields. This leads to interesting interactions: adsorption and desorption can be changed, as well as an in-situ control over the continuous gas separation on the nanometer scale can be done through membrane layers.